Pendampingan Penanaman Konsep Pembelajaran Matematika Berbasis Kontekstual Bagi Mahasiswa Calon Guru Sekolah Dasar : Pengabdian - Beatrix Purnama Sari; Andrian Runtius Lalang; Sefri Imanuel Fallo (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service (PKM) activity aimed to enhance PGSD students' understanding and skills in designing and implementing contextual-based mathematics learning (Contextual Teaching and Learning/CTL). As future elementary school teachers, they need pedagogical competencies aligned with students' concrete thinking stages. The program was conducted online in three stages: interactive webinars, mentoring through discussions and individual consultations, and a final evaluation through product assessment and participant reflection. Data were collected via pre- and post-tests, lesson plan (RPP) observations, and discussion documentation, and analyzed using descriptive quantitative and qualitative methods. Results showed a significant increase in average scores from 64.2 to 85.7, with 72% of participants successfully creating high-quality RPPs and LKPDs. Discussion forums and consultations proved effective in developing reflective and collaborative skills. This activity demonstrated that structured online mentoring is an effective strategy for preparing professional, innovative elementary school teacher candidates.